1996
DOI: 10.1111/j.1600-0676.1996.tb00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy‐reduced hepatic injury induced by ischemia/reperfusion in the rat

Abstract: In the present study, we investigated the role of the spleen in experimental hepatic ischemia/reperfusion in the rat. After a 90‐min period of ischemia in the left and middle hepatic lobes, the ischemia was released and the liver was reperfused for up to 24 h. Plasma alanine aminotransferase reached a peak 3 h after the onset of reperfusion, and gradually decreased thereafter. A histological examination revealed evidence of hepatocellular necrosis and degeneration, especially 24 h after the onset of reperfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 22 publications
3
34
0
Order By: Relevance
“…In addition, T cell-mediated effects could be amplified by other ectopic sites such as the spleen. In support of this hypothesis, a recent report by Okuaki et al (32) has demonstrated reduction of neutrophil infiltration and attenuation of I/R injury in splenectomized animals compared with controls. In the context of this present study, data suggest that Th17 cells at distant sites to the liver such as the spleen may be involved in the inflammatory process.…”
Section: Role Of Kupffer Cells and The Splenic Lymphocytes In Hepaticsupporting
confidence: 54%
“…In addition, T cell-mediated effects could be amplified by other ectopic sites such as the spleen. In support of this hypothesis, a recent report by Okuaki et al (32) has demonstrated reduction of neutrophil infiltration and attenuation of I/R injury in splenectomized animals compared with controls. In the context of this present study, data suggest that Th17 cells at distant sites to the liver such as the spleen may be involved in the inflammatory process.…”
Section: Role Of Kupffer Cells and The Splenic Lymphocytes In Hepaticsupporting
confidence: 54%
“…injection was superior suggesting that the splenic actions of these cells were important for the therapeutic benefit of this treatment [62]. Splenectomy significantly reduces ischemic injury in multiple organ systems including liver [63], GI tract [64], and kidney [65]. Recent results in our lab show that splenectomy prior to stroke reduces infarct volume by 80% [66]; similar to levels of protection seen in HUCBC therapies [61].…”
Section: The Role Of the Peripheral Lymphoid Organs In Strokesupporting
confidence: 73%
“…For example, it has been shown that rats splenectomized just prior to an ischemic insult to the liver demonstrated a reduction not only in neutrophil accumulation but also in biochemical and histological parameters of liver injury following 24 h of reperfusion. 24 Activation of lymphocytes at ectopic sites would be unaffected by FTY720 pretreatment, which could possibly account for the observed lack of effect on neutrophil recruitment. Additionally, the lymphocytosis observed in the untreated control group at 24 h of hepatic reperfusion may lend support to the notion that a systemic inflammatory response contributes to this process.…”
Section: Discussionmentioning
confidence: 95%